Antibacterial Activity of Aqueous Extracts of Anacyclus Pyrethrum (L) Link and Corrigiola Telephiifolia Pourr. From the Middle Atlas Region-Morocco - Amine, Daoudi; Mohamed, Bammou; Jamal, Ibijbijen; Laila, Nassiri (European Scientific Journal, ESJ, 2017)
Aqueous extracts of Corrigiola telephiifolia and Anacyclus pyrethrum were studied in vitro for their antimicrobial properties. These plants were collected from the Central Middle Atlas region. Corrigiola telephiifolia Pourr. and Anacyclus pyrethrum (L.) Link are widely used as a natural drug for the treatment of various infectious diseases. Phytochemical screening of the plants showed the presence of flavonoids, saponins, tannins, steroids and alkaloids. The determination of the polyphenols in the aqueous extract of the two plants revealed the presence of significant amounts of polyphenols (58.5 ± 0.76 mg equivalent of gallic acid (GEA) per gram of extract for C. telephiifolia, and 97.57 mg equivalent of gallic acid (GEA) per gram of extract of A. pyrethrum). The antimicrobial activity of the aqueous extracts against three bacterial strains was evaluated on the basis of the inhibition zone using the disk diffusion assay. The aqueous extract of Corrigiola telephiifolia is slightly active on E. coli. At a concentration of extract 100 μg mL-1, the size of the inhibition zone equal to 9 ± 0.06 mm. Whereas S. aureus, E. coli and K. pneumoniae showed a sensitivity to the macerate of Anacyclus pyrethrum at the concentration 100 μg mL-1 of extract with an inhibition zone 16.55 ± 0.6 mm, 14.95 ± 1.25 mm and 10.83 ± 0.96 respectively.